Persepsi Masyarakat Pengguna Pelayanan PT. Kereta Api Indonesia Unit Stasiun Lempuyangan Kota Yogyakarta (Studi Terhadap Pelayanan Stasiun dan Kereta Progo Kelas Ekonomi) - Kurnianingsih, Fitri; Edison, Edison (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2015)
Persepsi Masyarakat Pengguna Pelayanan PT. Kereta Api IndonesiaUnit Stasiun Lempuyangan Kota Yogyakarta(Studi Terhadap Pelayanan Stasiun dan Kereta Progo Kelas Ekonomi)   Fitri Kurnianingsih Edison (fitriacy@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH)   Abstract: Public services in the form of mass transport is an instrument of public mobility support and acceleration of the development. The train is one of the modes of transportation that are still popular and in the future will be increasingly popular to meet the public transport needs. This study aims to present a portrait of public transporation, especially the railway with objects and setting studies on service of Lempuyangan Train Station Yogyakarta and Train Progo economy class in 2010. The economy -class trains are a mainstay of mobility of the lower class and synony mous with low fares. But as a public service -which in delivery by PT. KAI-state-owned enterprises- the community remains entitled to the quality of service is good and decent. In fact, the principle has not been fully realized. This study presents the results of the quality of service PT. KAI is still low shown by the results of the analysis of user community services percetion captured in this survey.